MicroRNA in prostate, bladder, and kidney cancer: A systematic review - Catto, J; Alcaraz, A; Bjartell, A; De Vere White, R; Evans, C; Fussel, S; Hamdy, F; Kallioniemi, O; Mengual, L; Schlomm, T; Visakorpi, T (2011)
Context: MicroRNAs (miRNA) are noncoding RNAs that post-transcriptionally regulate gene expression. Their altered expression and function have been observed in most urologic cancers. MiRNAs represent potential disease biomarkers and novel therapeutic targets. Objective: To review and evaluate the evidence implicating miRNAs in the pathogenesis of prostate cancer (PCa), bladder cancer (BCa), and renal cancer. Evidence acquisition: A systematic review was performed using PubMed and Embase to search for reports using strings for microRNA, non-coding RNA, cancer, prostate, bladder, and renal cancer. Identified manuscripts were retrieved and references searched. Selected studies were required to concentrate on the role of miRNA in these urologic cancers. Evidence synthesis: We reviewed articles that focus on this topic. More than 40 miRNAs have been implicated in urologic cancer and many target common carcinogenic pathways. In particular, apoptosis avoidance, cell proliferation, epithelial-to-mesenchymal transition, angiogenic signalling, and the generation of androgen independence are targeted or facilitated by more than one miRNA. Little work has been done to evaluate the translational applications for this knowledge to date. Novel therapeutic strategies have been developed and are under investigation to selectively modulate miRNAs; such work would potentially enable personalised tumour therapy. Conclusions: MiRNAs appear to be important modulators of urologic cancer. Their expression is frequently altered in these tumours, and many are functionally implicated in their pathogenesis. They require evaluation to determine the translational role and therapeutic potential for this knowledge.